2021
DOI: 10.1093/cid/ciab502
|View full text |Cite
|
Sign up to set email alerts
|

Health of Asylees Compared to Refugees in the United States Using Domestic Medical Examination Data, 2014–2016: A Cross-Sectional Analysis

Abstract: Background Between 2008 and 2018, persons granted asylum (asylees) increased by 168% in the United States. Asylees are eligible for many of the same domestic benefits as refugees under the US Refugee Admissions Program (USRAP), including health-related benefits such as the domestic medical examination. However, little is known about the health of asylees to guide clinical practice. Methods We conducted a retrospective cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Increased migration from traditionally high hepatitis B endemic regions, such as Asian and African, to developed countries also contributes. 31 Our correlation analysis showed that HDI was significantly positively correlated with EAPC (either ASIR, ASMR, or SADR) when HDI > 0.8 ( Figure 6 ). Liu et al study indicated that a significant positive association between HDI and liver cancer incidence, by analyzing the burden of liver cancer disease from 1990 to 2016.…”
Section: Discussionmentioning
confidence: 78%
“…Increased migration from traditionally high hepatitis B endemic regions, such as Asian and African, to developed countries also contributes. 31 Our correlation analysis showed that HDI was significantly positively correlated with EAPC (either ASIR, ASMR, or SADR) when HDI > 0.8 ( Figure 6 ). Liu et al study indicated that a significant positive association between HDI and liver cancer incidence, by analyzing the burden of liver cancer disease from 1990 to 2016.…”
Section: Discussionmentioning
confidence: 78%